Assessment of inhalation errors, training time and patient preference for DuoResp® Spiromax® and Symbicort® Turbuhaler® in patients with asthma and COPD - Jordi Giner; Marta Villarnovo Cerrillo; Jaime Aboín Sierra; Laura Casas Herrero; Oliver Patino; Vicente Plaza (European Clinical Respiratory Journal, 2020)
While poor inhaler technique in asthma and chronic obstructive pulmonary disease (COPD) can compromise the effectiveness of inhaled medications, identifying and quantifying these errors may suggest ways to improve inhalation technique and patient outcomes. The objective of this international, multicentre care improvement programme was to investigate errors in inhaler use (handling errors and inhalation errors) made by patients in handling two dry powder inhalers; DuoResp® Spiromax® and Symbicort® Turbuhaler®. Patients with asthma or COPD aged between 18 and 80 years attending the allergology/pneumology departments of 14 hospitals in Spain and Portugal were included. All assessments were performed during one regular scheduled visit to the study clinic. Among 161 eligible patients (138 with asthma; 23 with COPD), inhalation errors were the most common type of error, with no significant difference between devices in overall total error rate, handling error rate or inhalation error rate. Significantly fewer total errors per patient (1.4 vs. 1.9; p < 0.001) and handling errors per patient (0.5 vs. 0.8; p < 0.001) were observed with DuoResp® Spiromax® compared with Symbicort® Turbuhaler®. The mean number of attempts for patients using DuoResp® Spiromax® to perform two correct procedures was 1.9 (0.6) compared with 2.1 (0.9) attempts for patients using Symbicort® Turbuhaler® (p = 0.016). Compared with Symbicort® Turbuhaler®, DuoResp® Spiromax® was found to be easy to learn how to use (p < 0.001), easy to prepare (p < 0.001), easy to use (p < 0.001), comfortable in terms of weight and size (p = 0.001), and patients felt that they were using the device correctly (p < 0.001). Overall, 79.5% of patients stated that they preferred DuoResp® Spiromax® as their first option over Symbicort® Turbuhaler®. The findings of this study may be useful in developing effective inhaler training programmes and thus improve outcomes in asthma and COPD.